Abscisic Acid and Gibberellins Antagonistically Mediate Plant Development and Abiotic Stress Responses - Shu, Kai; Zhou, Wenguan; Chen, Feng; Luo, Xiaofeng; Yang, Wenyu (Frontiers in Plant Science, 2018)
Phytohormones regulate numerous important biological processes in plant development and biotic/abiotic stress response cascades. More than 50 and 100 years have passed since the initial discoveries of the phytohormones abscisic acid (ABA) and gibberellins (GA), respectively. Over the past several decades, numerous elegant studies have demonstrated that ABA and GA antagonistically regulate many plant developmental processes, including seed maturation, seed dormancy and germination, root initiation, hypocotyl and stem elongation, and floral transition. Furthermore, as a well-established stress hormone, ABA plays a key role in plant responses to abiotic stresses, such as drought, flooding, salinity and low temperature. Interestingly, recent evidence revealed that GA are also involved in plant response to adverse environmental conditions. Consequently, the complex crosstalk networks between ABA and GA, mediated by diverse key regulators, have been extensively investigated and documented. In this updated mini-review, we summarize the most recent advances in our understanding of the antagonistically regulatory roles of ABA and GA in different stages of plant development and in various plant–environment interactions, focusing on the crosstalk between ABA and GA at the levels of phytohormone metabolism and signal transduction.